Potential of Using ROSA Centifolia to Remove Iron and Manganese in Groundwater Treatment - Abdul Kadir, Aslina; Othman, Norzila; M. Azmi, Nurul Azimah (International Journal of Sustainable Construction Engineering and Technology, 2012)
Groundwater is source for water supply because of its good natural quality. However, groundwater may be exposed toward to contamination by various anthropogenic activities such as agricultural, domestic and industrial. Groundwater quality problem are typically associated with high hardness, high salinity and elevated concentration of iron, manganese, ammonium, fluoride and occasionally nitrate and arsenic. Therefore, groundwater should be treated to acceptable level before consumption. This study is carried out with the objectives to optimize the feasibility condition of contact time, biosorbent dosage and pH range in removing heavy metal by using Rosa Centifolia (R. Centifolia) and also to determine the water quality of groundwater sources. A dried Rosa Centifolia pretreated before being used as biosorbent. Experiment was done by varying contact time, biosorbent dosage and pH range to get the optimum value. The removal characteristic of Iron and Manganese by Rosa Centifolia was analyzed using Atomic Absorption Spectrophotometer (AAS). The optimum condition is achieved at 240minutes, 0.05g/ml and pH 5 respectively. The optimum percentage removal of Iron and Manganese was found to be more than 70%. The finding indicated that Rosa Centifolia is a promising biosorbent in treating groundwater from RECESS UTHM well.